Studies development in Vilnius University the faculty of Mathematics and Informatics 1946–2008 - Verikaitė, Vitolda (Lietuvos matematikos rinkinys, 2008)
Article surveys the development of faculty (-ies). Statistics tables are made according to catalog of graduates.